Prevalence and diagnostic reliability of BRAF, RAS mutations, and RET/PTC rearrangements in a Latin American public health service population with thyroid nodular disease - Freddy David Moposita Molina; Grasiela Agnes; Marília Remuzzi Zandoná; Rogério Izquierdo; Fábio Alves Bilhar; Laura Berton Eidt; Virgílio Gonzales Zanella; Luiz Felipe Osowski; Sofia de Oliveira Belardinelli; Amanda Cometti de Andrade; Erika Laurini de Souza Meyer; Lenara Golbert; et al. (PLoS ONE, 2025)
Despite their high prevalence and generally benign nature in most cases, the investigation of thyroid nodules still presents potential diagnostic pitfalls, especially in cases with indeterminate cytology results. The performance of molecular markers of thyroid cancer may vary across centers and populations. This study aimed to verify the prevalence of mutations in the BRAF, and RAS genes, and RET/PTC rearrangements in patients undergoing fine-needle aspiration biopsy (FNAB) for thyroid nodule evaluation in a real-world public health service population. Point mutations and rearrangements were detected by Sanger DNA sequencing. A total of 231 thyroid nodules in 220 patients were evaluated, being 86.8% females and a mean age of 55.6 ± 13.9 years. For molecular analysis, high-quality DNA and RNA were obtained from 200 samples. Mutations or rearrangements in target genes were identified in 14% of the 200 samples evaluated. The frequency of the BRAF-like mutations was 5.5%, detected in 9 out of 17 malignant nodules (52.9%) and one in a benign nodule (0.7%). Fourteen RAS-like mutations were identified in benign nodules (57.1% HRAS, 21.5% NRAS and 21.5% KRAS) and only one was present in a malignant nodule (5.9%). Considering only nodules with indeterminate cytology (Bethesda III and IV, n = 53), 9 mutations were detected, 6 in benign histology (all RAS-like), 1 in malignant histology (BRAF-like), and 2 still unoperated, therefore without a histopathological diagnosis. This research concludes that the presence of the BRAF V600E mutation could be useful in supporting the diagnosis of thyroid cancer, due to its high positive predictive value, since 89% of nodules with BRAF V600E mutation were malignant. Additionally, clinical criteria should be established to determine which nodules with RAS-like mutations require closer follow-up, particularly those with indeterminate cytology.